Digital Native Meet Friendly Visitor: A Flexner-Inspired Call to Digital Action. (13th July 2016) - Wolf, Lea; Goldkind, Lauri
ABSTRACT: A century ago, Abraham Flexner offered his perspective on the nascent field of social work, describing the field as educationally unfocused, too diversified in its practices, and too relational or assistive to other fields to meet the criteria for professional status. Using the example of the imperative to integrate information and communication technologies (ICT) into social work practice, we examine the ways these 100-year-old challenges persist as well as how they are being challenged and reworked. Drawing on three central themes from Flexner—education, diversity of professional settings and functions, and the relational nature of the work—we examine the absence of ICTs in social work practice, arguing that a lack of curricular exposure to ICT tools, strategies, and thinking at the BSW and MSW levels and a failure to incorporate these technologies with clients, agencies, and communities leads to a damaging disjunction between professionals and a changing culture. We suggest that the challenge proffered to social work by technology provides a radical opportunity to create a more socially just practice, offer a preliminary list of best practices for approaching ICT integration, and make suggestions for further inquiry.